Volumetric Proton Spectroscopic Imaging of Mild Traumatic Brain Injury - Govindaraju, Varanavasi; Gauger, Grant E.; Manley, Geoffrey T.; Ebel, Andreas; Meeker, Michele; Maudsley, Andrew A. (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Poor clinical outcomes without notable neuroimaging findings after mild traumatic brain injury (MTBI) suggest diffuse tissue damage and altered metabolism not observable with conventional MR imaging and CT. In this study, MTBI-associated metabolic changes were assessed over the entire brain by using volumetric proton MR spectroscopic imaging (MRSI) and the findings related to injury and outcome assessments.METHODS: Fourteen subjects with mild closed head injury (Glasgow Coma Scale [GCS] scores of 13–15) underwent structural MR imaging and proton MRSI at 1.5 T within 1 month of injury. Distributions of N-acetylaspartate (NAA), total creatine (Cr), and total choline (Cho) were mapped over a wide region of the brain, and metabolite ratios were calculated for 25 regions without MR imaging abnormalities. Results were compared with data from 13 control subjects.RESULTS: Significant changes (P < .05) were found for some, but not all, brain regions for the average values from all MTBI subjects, with reduced NAA/Cr, increased Cho/Cr, and reduced NAA/Cho. Global NAA/Cho obtained from the sum of all sampled regions in two subjects was significantly reduced. Metabolite ratios were not significantly correlated with GCS score at admission or Glasgow Outcome Scale (GOS) score at 6 months after injury, although they were weakly correlated with GOS score at discharge.CONCLUSION: These results show evidence of widespread metabolic changes following MTBI in regions that appear normal on diagnostic MR images. Although the association with injury assessment and outcome is weak, this preliminary study demonstrates the applicability of volumetric proton MRSI for evaluating diffuse injury associated with MTBI.